Parafunctions of triangular matrices and m-ary partitions of numbers - Stefluk, S.; Zatorsky, R. (Algebra and Discrete Mathematics, 2016)
Using the machinery of paradeterminants and parapermanents developed in [2] we get new relations for some number-theoretical functions natural argument that were studied in [3].